2007
DOI: 10.1002/pssa.200776327
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardness of diamond and silicon sensors compared

Abstract: PACS 29.40.Wk, 42.88.+h, 61.80.x, 81.05.UwThe radiation hardness of silicon charged particle sensors is compared with single crystal and polycrystalline diamond sensors, both experimentally and theoretically. It is shown that for Si-and C-sensors, the NIEL hypothesis, which states that the signal loss is proportional to the Non-Ionizing Energy Loss, is a good approximation to the present data. At incident proton and neutron energies well above 0.1 GeV the radiation damage is dominated by the inelastic cross se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 6 publications
3
60
0
Order By: Relevance
“…A reduction of the maximum CCD (at high fields) was not observed after irradiation, as expected from the high radiation hardness observed in test beams [5].…”
supporting
confidence: 66%
“…A reduction of the maximum CCD (at high fields) was not observed after irradiation, as expected from the high radiation hardness observed in test beams [5].…”
supporting
confidence: 66%
“…Various neutron reactions with 12 C are possible at energies up to 14 MeV which subsequently lead to the emission of α-particles as one of the reaction products [32] and deposit a larger amount of energy per unit path length in the detector than a neutron of equivalent energy.…”
Section: Resultsmentioning
confidence: 99%
“…Radiation damage studies on this high quality synthetic single crystal diamond material have begun to evaluate and gain understanding of the effects of radiation induced defects on the detection performance. [2,11,12] The signal of a radiation detector operated as a solid state ionisation chamber is formed by the integrated induced current, i.e. the induced charge, at the electrodes of the detector by the movement of free charge carriers within the device towards those electrodes under the electric field they experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difference between the two types of diamonds are their sizes of ∼0.25 cm 2 for scCVD and up to 6 inch for pCVD and the smaller signal in pCVD [5]. In various studies it was shown that compared to corresponding silicon detectors, diamond is at minimum three times more radiation hard [6], has at least a two times faster charge collection [7] and its thermal conductivity is four times higher [8].…”
Section: Introductionmentioning
confidence: 99%